Selforganisation and dynamics peculiarities of intense electron beams in compact crossed fields systems - Agafonov, A.V.; Tarakanov, V.P.; Fedorov, V.M. (Вопросы атомной науки и техники, 2001)
The review of the results of computer simulations of electron flow self-organisation inside magnetically isolated coaxial diodes (magnetron gun) is given. Magnetron guns of usual and inverted polarities are considered.